KONTRIBUSI RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN BERAU: KONTRIBUSI RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN BERAU - IRA INDRIANI (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2022)
The purpose of the research carried out was to determine the contribution of regional levy receipts to regional original revenue receipts in Berau Regency in 2013 to 2019. The benefits that researchers expect from the results of this study include being able to add insight and understanding of regional levies. For policy makers, this research is expected to be used as a material for consideration and input in an effort to increase the acceptance of regional levies in order to encourage an increase in PAD in Berau Regency. The conclusion from the results of the study shows that the acceptance of the contribution of regional levies during 2013 to 2019 has less effect on regional original income where the average acceptance of regional levies on regional original income is included in the